Hubungan Konsep Diri dengan Kenakalan Remaja di SMA Negeri 2 Palembang Tahun 2025: Penelitian - Riko Sandra Putra; Ratna Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Adolescents are vulnerable to delinquency, especially if they have a negative self-concept that triggers deviant behavior. This study aims to determine the relationship between self-concept and juvenile delinquency at SMA Negeri 2 Palembang. The study used a quantitative method with a cross-sectional approach. The sample consisted of 221 respondents selected by simple random sampling. The instruments used were the Tennessee Self-Concept Scale (TSCS) to measure self-concept and the Self-Report Delinquency Scale (SRD) to measure juvenile delinquency. Data analysis was conducted using the chi-square test. The results showed that out of 208 respondents, 87.5% had a positive self-concept and 12.5% had a negative self-concept. There was a significant relationship between self-concept and juvenile delinquency with a p-value = 0.000 (< 0.05). Adolescents with a positive self-concept tended to have low levels of delinquency, while those with a negative self-concept showed moderate levels of delinquency. Based on the results of this study, it is recommended that various parties, especially families, schools, and health services, play an active role in helping adolescents build a positive self-concept. Adolescents are also expected to be more open with themselves and their environment, and to seek professional help such as guidance counselors or psychologists when experiencing emotional or social pressure.